Insights in Breast Cancer: A Review - Chiripireddy Saichandana, (Asian Journal of Pharmaceutics (AJP), 2024)
Breast cancer is the most common cancer affecting women in India, with increasing incidence and mortality rates in recent years. This review addresses the specific challenges associated with breast cancer in the Indian setting, including its epidemiology, risk factors, and disparities in healthcare. In India, the disease tends to be diagnosed at a younger age and at more advanced stages compared to Western populations, primarily due to factors such as limited awareness, cultural stigma, and restricted access to healthcare services. Delays in diagnosis, socioeconomic challenges, and the absence of widespread screening programs further complicate the issue. Although recent public health initiatives, including awareness campaigns and the establishment of screening and treatment facilities, have shown progress, significant gaps remain in early detection, individualized treatment, and survivorship care. This review underscores the need for targeted strategies, improved healthcare infrastructure, and equitable access to diagnostic and therapeutic resources to reduce the impact of breast cancer in India and enhance patient outcomes.